AN EXPLORATORY STUDY TO INVESTIGATE THE USE OF AUGMENTED REALITY IN SUPPORTING COLLABORATIVE LEARNING PROCESSES - MATCHA, WANNISA (2013)
Collaborative learning mediated by technology was proven as one ofthe efficient learning approaches which benefit in both academic and soft skills. Despite advantages offered by technologies, some obstacles were also created e.g. problem in supporting interaction and communication, disregard of physical and sharing objects' roles. Augmented Reality (AR) offers a unique learning experience by combining the physical and virtual object. The benefits of rich media were enduring and the role of physical material is also considered. However, the literature reveals that there is no design guideline specifically intended for AR based collaborative learning. Hence, this research aims to study and proposed a conceptual framework to guide the development of collaborative AR in learning.